A single point mutation in the embB gene is responsible for resistance to ethambutol in Mycobacterium smegmatis. - Lety, M A (1997)
Ethambutol [EMB; dextro-2,2'-(ethylenediimino)-di-1-butanol] is an effective drug when used in combination with isoniazid for the treatment of tuberculosis. It inhibits the polymerization of arabinan in the arabinogalactan and lipoarabinomannan of the mycobacterial cell wall. Recent studies have shown that arabinosyltransferases could be targets of EMB. These enzymes are encoded by the emb locus that was identified in Mycobacterium smegmatis, Mycobacterium leprae, Mycobacterium avium, and Mycobacterium tuberculosis. We demonstrate that a missense mutation in the M. smegmatis embB gene, one of the genes of the emb locus, confers resistance to EMB. The level of resistance is not dependent on the number of copies of the mutated embB gene, indicating that this is a true mechanism of resistance. The mutation is located in a region of the EmbB protein that is highly conserved among the different mycobacterial species. We also identified in this region two other independent mutations that confer EMB resistance. Furthermore, mutations have recently been described in the same region of the EmbB protein from clinical EMB-resistant M. tuberculosis isolates. Together, these data strongly suggest that one of the mechanisms of resistance to EMB consists of missense mutations in a particular region of the EmbB protein that could be directly involved in the interaction with the EMB molecule.